DEVELOPMENT OF SCIENTIFIC IDEAL OF INTELLIGENCE IN TED HUGHES'S POETRY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2019)
The development of scientific ideal of intelligence has persuaded human beings to identify themselves with what is no more than a narrow and superficial vision of life. Scientific morality negates emotionality and makes him to follow utilitarian viewpoint, which places utility above beauty and other tender aspects of life. The animal world, no matter, how closely observed and portrayed in Hughes's poetry, is secondary to his concern with human life. He presents man in multiple contexts, in relation to animals, to nature and to his own personal and self-complacency. Man-woman relationships have been a matter of grave concern for him, overtly as well as symbolically.